NATO's future : implications for U.S. military capabilities and postures - Ochmanek, David A. (RAND, 2000)
Events after the collapse of the Soviet Union and the end of the Cold War have shown the need for a transformed NATO capable of a wide range of missions, including projecting stability around the periphery of the NATO treaty area, intervening in civil conflicts, coordinating power-projection operations, and countering weapons of mass destruction. The author's analysis finds that the military forces of NATO's member states should be ready for expeditionary operations, which will require expanding and modernizing forces; NATO must be able to deter and defeat chemical, biological, and nuclear weapons; and U.S. forces in Europe are invaluable assets for shaping behaviors and expectations in the region and for responding to challenges in and around Europe. The future will demand effective and coordinated action by nations with common interests, and for the United States and its allies, NATO is by far the best vehicle available. A key factor will be the Europeans' willingness to accept greater responsibility for the defense of common interests outside of the treaty area, perhaps beyond Europe itself. Investment in military capabilities as needed is called for.